Work Breaks during Minimally Invasive Surgery in Children: Patient Benefits and Surgeon's Perceptions - Engelmann, Carsten; Schneider, Mischa; Grote, Gudela; Kirschbaum, Clemens; Dingemann, Jens; Osthaus, Alexander; Ure, Benno (European Journal of Pediatric Surgery, 2012)
Introduction We recently reported that 5-minute work breaks every 25 minutes during long lasting laparoscopy in children (intermittent pneumoperitoneum [IPP] scheme) decrease the surgeon's stress markers such as saliva cortisol and heart rate and improve time-concentration scores significantly. Data on the impact of breaks on the patient and on the surgeon's perception of breaks, however, are still lacking.Materials and Methods We present the comprehensive biometry data of a randomized trial including 26 patients operated with (IPP) and 26 patients without breaks (continuous pneumoperitoneum [CPP]). Moreover, we analyzed the surgeon's perception of the break scheme using behaviorally anchored 10-point rating scales.Results There were no significant intergroup differences in the pooled patients' hemodynamics including cardiac output, blood gas readings, and temperature during and after the operation. Infants <1 year of age undergoing IPP versus CPP produced significantly higher urine volumes (1.60 ± 1.8 vs. 0.67 ± 1.00 mL/h/m2, p < 0.05). The overall area under the curve (AUC) of their cardiac output was 106.7 ± 41.1 (IPP) versus 78.0 ± 41.3 (CPP). This difference became significant during long operations (p < 0.05 for AUC 150 to 270 minutes). Surgeon's break perception and acceptance: team communication shifted from an implicit “mute communication” to an explicit way “issues are outspoken” by +4.7 ± 2.6 (p < 0.05) with improved coherence between operator and assistants (+3.9 ± 2.1). However, when questioned whether there was one particular welcome (5.1 ± 1) or extremely disturbing (6.4 ± 2.4) break during the entire procedure, the latter yielded a higher score (p > 0.05). Acceptance varied according to the surgeon's own esteem of his/her work style. Operators with high self-ratings for “fast” were inclined to put up with shorter breaks (“fast” vs. “slow” = 3.5 ± 1.4 vs. 5.5 ± 0.7, p < 0.05). Overall the scheme was approved (5.9 ± 3.2).Conclusions A break scheme has no detrimental effect on patient physiology and is beneficial in infants. It needs careful tailoring to both the surgeon's work situation and self-esteem to gain acceptance.
Keywords: intraoperative breaks; physiology; effects of pneumoperitoneum; laparoscopy